2017
DOI: 10.1007/s00415-017-8487-y
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict benign multiple sclerosis? Results of a 20-year long-term follow-up study

Abstract: Benign multiple sclerosis (MS) is a discussed clinical entity, with variable reported prevalence (6-64%) requiring at least 5-10 years of clinical observation. Moreover, many benign patients progress with time becoming no longer benign (NLB). The objective of this study is to compare benign MS patients (EDSS ≤3, 10 years from disease onset) who still fulfilled the definition at 20 years to those NLB. In our retrospective study based on Ottawa Hospital MS Clinic database, 175 benign patients fulfilled the inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…One commonly cited definition has been an Expanded Disability Status Scale (EDSS) score of ≤3 at 10 years from symptom onset, but around one quarter of patients meeting this definition accumulated further disability when followed up to 20 years 2–8. Recent studies have suggested that a low EDSS status after 15 years of MS may be a more reliable marker of benign status 6 9…”
Section: Introductionmentioning
confidence: 99%
“…One commonly cited definition has been an Expanded Disability Status Scale (EDSS) score of ≤3 at 10 years from symptom onset, but around one quarter of patients meeting this definition accumulated further disability when followed up to 20 years 2–8. Recent studies have suggested that a low EDSS status after 15 years of MS may be a more reliable marker of benign status 6 9…”
Section: Introductionmentioning
confidence: 99%
“…In severe cases (i.e., Marburg's variant of MS), inflammatory demyelination can lead to severe functional deficits and sometimes dead (Nunes et al, ; Rush, MacLean, & Freedman, ). Some cases of MS are more benign, with no worsening of functional ability, even after 15 years of diagnosis, and low annualized relapse rates (Glad, Nyland, Aarseth, Riise, & Myhr, ; Sartori, Abdoli, & Freedman, ). However, in most cases, these attacks can recur with increasing frequency and proceed to secondary progressive MS, which, as with primary progressive forms, involves axonal damage and neurodegeneration (Charcot, ; Kornek et al, ; Trapp, Ransohoff, & Rudick, ) resulting in irreversible clinical disability.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the disease course was classified as benign if the EDSS remained ≤2 at least 10 years after the first demyelinating event. This definition has recently been demonstrated to predict subsequent benign course also for another ten years, 3 thus increasing the reliability of the definition. Previously, in the absence of the changes in EDSS or brain magnetic resonance T2 lesion load, cardiac autonomic function was suggested to reflect subclinical activity in MS during 2 years follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…The disease course was classified according to the EDSS score determined at a stable phase. Patients with EDSS score ≤2 after a minimum of ten years follow-up after the onset symptom were classified as benign 3 RRMS group and patients with EDSS score >2 were classified as disabling RRMS group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation